Pemberdayaan Perempuan Dalam Meningkatkan Pendapatan Keluarga Di Desa Beran Kecamatan Ngawi Kabupaten Ngawi - Sumiati, Sumiati (JURNAL SOSIAL : Jurnal Penelitian Ilmu-Ilmu Sosial, 2020)
The purpose of this study is to describe women's empowerment in increasing family income in Beran Village, Ngawi District, Ngawi Regency. This type of research is descriptive, aiming to describe women's empowerment in increasing family income in Beran Village, Ngawi District, Ngawi Regency. Respondents in this study were pre-prosperous families in Beran Village, Ngawi Subdistrict, Ngawi Regency, amounting to 57 people. Data collection techniques in this study used questionnaires and documentation. While the data analysis technique uses qualitative descriptive analysis. The research findings show that: (1) The level of welfare in the empowerment of women in increasing family income in Beran Village, Ngawi District, Ngawi District is categorized as good; (2) The level of access to women's empowerment in increasing family income in Beran Village, Ngawi District, Ngawi District is categorized as good; (3) The level of connectivity in empowering women in increasing family income in Beran Village, Ngawi District, Ngawi Regency is categorized as good; (4) The level of participation in empowering women in increasing family income in Beran Village, Ngawi District, Ngawi Regency is categorized as good; (5) The level of equality of power in empowering women in increasing family income in Beran Village, Ngawi District, Ngawi Regency can be categorized as good; and (6) Empowering women in increasing family income in Beran Village, Ngawi District, Ngawi Regency can be categorized as good.Â Keywordsâ€”: women's empowerment; family income.